O risco e sua alteração nos seguros de dano - Carvalho, Carlos Eduardo Staudacher Leal de (2024)
This paper aims to examine the risk and its variation during the execution of insurance contracts, analyzing the current legislation, regulatory standards, doctrine, jurisprudence and documents. In the first part of the work, we seek to systematize the study of the relevant risk to insurance, the most essential of the five elements of this contract. Therefore, analyzing the process that determines its entry into insurance, addressing and problematizing the entire process of contract formation, not only in light of current legislation and regulations, but, whenever relevant, with eyes on prospective law, that is, the Bill nº 2,597, of 2024, which seeks to implement a special law for insurance in Brazil, and the draft law to update the Civil Code, which also proposes important changes to the chapter regarding this contract. Still in the first part of the paper, the characteristics and contours of insurance risk are presented. In the second part, the paper focuses on changes in risk after the conclusion of the contract, examining the functions and general requirements of the legal regime relevant to these changes (CC, arts. 768, 769 and 770). Risk aggravation is analyzed critically, presenting its modalities, requirements and effects, as well as criticizing the jurisprudence formed on the subject and on this prospective law. The hypotheses and effects of risk reduction and its disappearance after the conclusion of the contract are also investigated. Finally, in the third and last chapter, the work exposes criticism to the provisions of Bill 2,597, of 2024, and the draft law to update the CC on the risk and the regime regarding its changes in the stage of execution of damage insurance